Analysis of the Influence of Pharmaceutical Service Quality and Hospital Image on Patient Satisfaction and Its Impact on Outpatient Revisit Interest at XYZ Hospital - Ni Kadek Doni; Maura Linda Sitanggang; Derriawan, Derriawan (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
To improve the quality of pharmaceutical installation services in hospitals, there needs to be a service standard that can be used as a guideline in providing pharmaceutical services. By implementing service standards optimally, it will foster a positive hospital image. A positive hospital image will foster patient loyalty and interest in revisiting. This study aims to analyze the effect of pharmaceutical service quality and hospital image on patient satisfaction and its impact on the interest in revisiting outpatients at XYZ Hospital. This research method uses a quantitative descriptive approach. This study is included as explanatory research. The total sample in this study was 250 respondents. The sample was determined based on simple random sampling. The data analysis technique used in this study was descriptive statistical analysis and the Partial Least Square (PLS) test which includes outer model analysis (measurement model) and inner model analysis (structural model). The data was processed using Smart PLS software version 3. SEM ( Structural Equation Modeling ) based on variance. The results show that the quality of pharmaceutical services has a significant effect on patient satisfaction, the image of the hospital has a significant effect on patient satisfaction, the quality of pharmaceutical services has a significant effect on the intention to revisit, the image of the hospital has a significant effect on the intention to revisit, patient satisfaction has a significant effect on the intention to revisit, the quality of pharmaceutical services has a significant effect on the intention to revisit and the image of the hospital has a significant effect on the intention to revisit through patient satisfaction. So it can be concluded that the quality of service and the image of the hospital affect patient satisfaction and the intention to revisit patients, the better the quality of service and the image of the hospital, the higher the level of satisfaction and the intention to revisit the patient.